Progress in molecular diagnosis and treatment of chronic mucocutaneous candidiasis - Jing, Danrui; Liang, Guanzhao; Li, Xiaofang; Liu, Weida (Frontiers in Immunology, 2024)
Chronic mucocutaneous candidiasis (CMC) is characterized by recurrent or persistent infections with Candida of the skin, nails, and mucous membrane. It is a rare and severe disease resulting from autoimmune defects or immune dysregulations. Nonetheless, the diagnosis and treatment of CMC still pose significant challenges. Erroneous or delayed diagnoses remain prevalent, while the long-term utility of traditional antifungals often elicits adverse reactions and promotes the development of acquired resistance. Furthermore, disease relapse can occur during treatment with traditional antifungals. In this review, we delineate the advancements in molecular diagnostic and therapeutic approaches to CMC. Genetic and biomolecular analyses are increasingly employed as adjuncts to clinical manifestations and fungal examinations for accurate diagnosis. Simultaneously, a range of therapeutic interventions, including Janus kinase (JAK) inhibitors, hematopoietic stem cell transplantation (HSCT), cytokines therapy, novel antifungal agents, and histone deacetylase (HDAC) inhibitors, have been integrated into clinical practice. We aim to explore insights into early confirmation of CMC as well as novel therapeutic options for these patients.